(untitled) (Revista Ciência Agronômica, 2018)
The environmental factors that affect the morphological characteristics of different genera of cacti are little known. The aim of this study therefore was to analyse the contribution of environmental variables to growth in cladodes and plant of forage cactus clones of the genera Nopalea and Opuntia. The data used in this study were obtained from an experiment conducted in Serra Talhada, Pernambuco, Brazil, between 2012 and 2013, where the clones ‘IPA Sertânia’ (Nopalea), ‘Miúda’ (Nopalea) and ‘Orelha de Elefante Mexicana’ (Opuntia) were submitted to different irrigation depths (2.5, 5.0 and 7.5 mm) and fixed irrigation intervals (7, 14 and 28 days). Morphological characteristics of the cladodes and plants and weather variables were obtained over time. Pearson’s correlation, followed by multicollinearity, canonical and path analysis were applied. The minimum temperature, maximum and minimum relative humidity, wind speed and solar radiation were the variables that most affected growth in the cactus. The genus Opuntia showed less sensitivity to variations in air temperature compared to the genus Nopalea. The higher intensities of global solar radiation affected clones of the genus Nopalea more than the genus Opuntia. It can be concluded that there are different environmental requirements between forage cacti of the genera Nopalea and Opuntia.